Students’ perception of the programme offered by the School of Biosciences and Biotechnology, Faculty of Science and Technology, UKM - Ainon Hamzah; Kalaivani Nadarajah; Mahanem Mat Noor; Arina Anis Azlan (penerbit ukm, 2015)
This study was conducted to gauge students’ competency and satisfaction in employment preparation within programmes offered by the School of Biosciences and Biotechnology, at the Faculty of Science and Technology, Universiti Kebangsaan Malaysia (UKM). A survey questionnaire was distributed to all final year students of the School and 128 of them responded. The results showed that for the programme components, respondents were most satisfied with the quality of academic staff, followed by the quality of fellow students, curricular contents and overall learning environment. In terms of knowledge, general skills, and virtues they received, the respondents expressed high competency levels in various areas which include the languages, English and Bahasa Melayu, interpersonal skills, information technology and research skills, and work related skills gained through industrial training attachment. However, respondents rated the overall academic experience to be of average standing. These findings indicated that the curricular contents need to be reviewed to improve/enhance the quality of the programmes offered in order to prepare students for demanding expectations of the job market.